ANALYSIS OF FLOOD MANAGEMENT STRATEGIES BASED ON INFRASTRUCTURE STRENGTHENING AND ENVIRONMENTAL CONSERVATION IN SOUTH KALIMANTAN - Aswin Rosadi; Budi Kristanto (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2025)
Flooding in South Kalimantan has become increasingly severe due to deforestation, inadequate infrastructure, and urbanization. This study analyzes strategies to mitigate floods through infrastructure strengthening and environmental conservation. Using a mixed-methods approach, the research identifies deforestation as a primary driver of flood risk, reducing the land's water absorption capacity and worsening runoff. Urban areas, particularly Banjarmasin and Martapura, experience recurrent floods due to outdated drainage systems incapable of handling extreme rainfall exacerbated by climate change. Infrastructure improvements, such as modernized drainage systems, dams, and embankments, are crucial but must be supported by conservation efforts. Reforestation, river restoration, and sustainable watershed management significantly reduce flood risks by enhancing ecological resilience. Collaborative governance involving government agencies, local communities, and private sectors is essential to address resource limitations and improve flood preparedness. This integrated approach combines infrastructure development and ecosystem-based solutions to create sustainable, long-term flood mitigation strategies. By prioritizing environmental restoration, adaptive infrastructure, and multi-stakeholder collaboration, South Kalimantan can enhance its resilience against flood disasters.